Comportamento mecânico de geocélulas preenchidas com resíduos de pedras preciosas - Baruffi, Aline (2017)
The waste from the processing of precious stones consists of refuse, semi-finished parts and and defects pieces, which end up being stored the companie’s courtyard, which can cause risks to the environment. Studies have shown that it is possible to use this waste in civil engineering, such as cement materials, urban pavement structures and cuttings, thus contributing to the reduction of waste stored in companies. Another possibility of reusing this material is through the filling of geocells. The geocells have the function of increasing the capacity of the soi l, which are composed of series of interconnected cells forming a three-dimensional structure that confines the materials inserted therein. In this context, the objective of this work is to analyze the mechanical performance of the geocell, by means of plaque tests, using as fill material the residue of precious stones processing, from the municipality of Soledade / RS. The proposed experimental program aimed to characterize the residue, to analyze the behavior of the soil without reinforcement and reinforced with geocells of 5cm, 10cm and 20cm of height when submitted to applied loads and, finally, to compare the data obtained in the tests with the most usual methods of prediction of carrying capacity for geocells. The residue is classified as sand and silt, with 35% of fine materials, specific mass equal to 2.62g / cm³, specific apparent dry mass 1.91g / cm³ and optimal humidity equal to 11.29%. The results show that the geocellular reinforced soil presents an improvement in the load capacity of at least 36%, in addition to significantly reducing soil repression. The use of geocells of higher heights is ideal for increasing load capacity, and for reducing geocells with lower heights are the most indicated. The position of the plate in the geocelle influences its behavior, when located at the cell attachment node provides a load capacity gain greater than 77% than when allocated at the center of the cell. The method proposed by Presto (2008) was the most suitable for the estimation of the load capacity of this work.